The effect of boron concentration on the structure and elastic properties of Ru-Ir alloys: first-principles calculations. (6th April 2018) - Li, Xiaolong; Zhou, Zhaobo; Hu, Riming; Zhou, Xiaolong; Yu, Jie; Liu, Manmen
Abstract: The Phase stability, electronic structure, elastic properties and hardness of Ru-Ir alloys with different B concentration were investigated by first principles calculations. The calculated formation enthaplies and cohesive energies show that these compounds are all thermodynamically stable. Information on electronic structure indicates that they possess metallic characteristic and Ru-Ir-B alloys were composed of the Ru-B and Ir-B covalent bond. The elastic properties were calculated, which included bulk modulus, shear modulus, Young's modulus, Poisson's ratio and hardness. The calculated results reveal that the plastic of Ru-Ir-B alloys increase with the increase of the content of B atoms, but the hardness of Ru-Ir-B alloys have no substantial progress with the increase of the content of B atoms. However, it is interesting that the hardness of the Ru-Ir-B compound was improved obviously as the B content was higher than 18 atoms because of a phase structure transition.